2019
DOI: 10.3390/agronomy9120868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postponing Topdressing-N on the Yield of Different Types of japonica Rice and Its Relationship with Soil Fertility

Abstract: N fertilizer is usually supplied via multiple applications in rice production in China. Due to the high N-recovery efficiency (NRE) of panicle fertilizer, applying large amounts of fertilizer at the booting stage is considered to be an effective measure of increasing yields, although it has adverse effects on eating quality. In this study, using six inbred and four hybrid japonica varieties, we postponed topdressing-N to increase the ratio of panicle N from 20% to 40% by correspondingly reducing the N amount a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…These findings show that the study of drip irrigation rice is of great value for promoting largescale upland rice production and improving water and nitrogen utilization efficiency in arid areas. However, the yield and NUE of the two cultivars were not significantly different from those under alternate dry−wet irrigation, which may be related to the cultivars (Jehangir et al, 2022), ecological conditions (Naeem et al, 2022), soil types (Ye et al, 2019), and cultivation methods (Sandhu and Mahal, 2014).…”
Section: Appropriate Water and Nitrogen Management Increases The Yiel...mentioning
confidence: 90%
“…These findings show that the study of drip irrigation rice is of great value for promoting largescale upland rice production and improving water and nitrogen utilization efficiency in arid areas. However, the yield and NUE of the two cultivars were not significantly different from those under alternate dry−wet irrigation, which may be related to the cultivars (Jehangir et al, 2022), ecological conditions (Naeem et al, 2022), soil types (Ye et al, 2019), and cultivation methods (Sandhu and Mahal, 2014).…”
Section: Appropriate Water and Nitrogen Management Increases The Yiel...mentioning
confidence: 90%
“…The seed yield of grass species is greatly dependent on inflorescence morphological traits, starting with spikelets per inflorescence and seeds per spikelet, to kernel size, and then to awns (Dreccer et al, 2019;Severova et al, 2022). Besides, Seed yield in grasses is also known to be associated with a number of seed yield components, such as by fertile tillers m −2 , spikelets per fertile tiller, seed number per plant and 1000-grain weight seed yield (Bhutto et al, 2016;Vafa et al, 2021;Ye et al, 2019). These traits are important and complex to realize high seed yields.…”
Section: Nitrogen Use Efficiencymentioning
confidence: 99%
“…Zhu et al (2017) and Liang et al (2021) revealed that rice yield first increased and then decreased with increasing N application rate [37,38], and we reached a similar conclusion (Figure 1A-C). Ye et al (2019) indicated that N application at a later stage of rice reduced the panicle number and was not conducive to increasing grain yields [39]. However, Li et al (2018) reported that increasing the proportion of panicle N fertilizer improved N use efficiency and increased grain yield [40].…”
Section: Effects Of N Regime In the Main Crop On The Yield Of The Mai...mentioning
confidence: 99%